Maximum Power Photovoltaic Units Penetration under Voltage Constraints Criteria in Distribution Network Using Probabilistic Load Flow. (January 2019) - Anastasiadis, Anestis G.; Kondylis, Georgios P.; Papadimitriou, Christina; Polyzakis, Apostolos; Vokas, Georgios; Psomopoulos, C.S.
Abstract: Nowadays, the connections of Renewable Energy Sources to Distribution Networks are increasing in large number. In order to assess the performance of Distribution Network under normal operating conditions Probabilistic Load Flow analysis is necessary in order to take into consideration the stochastic behavior of Load Demands and Renewable Energy Sources (for example the Photovoltaics Generation Units). Generally, Deterministic Load Flow calculations are typically needed to assess the allowed Distributed Generation penetration level for a given network in order to ensure, for example, that Voltage limits are not exceeded. The present paper deals with the Probabilistic Load Flow using Monte Carlo techniques. The developed program allows probabilistic predictions of Voltages profiles at all buses or nodes of a Distribution Networks. A practical case is also discussed to show the application of the study in order to assess the maximum Photovoltaic power penetration that can be installed into a Distribution Network without violating Voltage Constraints.